The Impact of Covid-19 on the Digitalization of Micro, Small and Medium Enterprises - Muhammad Iffan; Retna Fadhilah; Isti Adzah Tarapti; Fitri Shaharani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The purpose of this research is to find out the impacts the coronavirus pandemic has on digitization in the Micro, Small, and Medium Enterprises business world. The method used for this research was a descriptive method with a qualitative approach. The results show that various ways have been done by Micro, Small, and Medium Enterprises actors in dealing with this pandemic, such as by selling offline, online, or a combination of the two. However, internet access and the digital readiness index of these business actors show that these Micro, Small, and Medium Enterprises are not fully ready to immediately switch to digital. Based on data, most of Micro, Small, and Medium Enterprises have started trying to sell online. The decrease in turnover of Micro, Small, and Medium Enterprises and cooperatives due to Covid-19 has been very significant since its appearance at the end of 2019 so that innovation is needed to be able to run the UMKM business. The use of the internet is felt to help Micro, Small, and Medium Enterprises to run a business, especially during a pandemic.